Cultivating critical consciousness through a Global Health Book Club - Collins, Sarah L.; Case, Stuart J.; Rodriguez, Alexandra K.; Allen, Acquel C.; Wood, Elizabeth A. (Frontiers in Education, 2023)
Central to public health practice is mindfulness and intentionality toward achieving social justice and health equity. However, there is limited literature published on how educators are integrating these concepts into their curricular, pedagogical and instructional efforts. To promote a social justice-based, health equity-focused, and critical pedagogically-grounded learning environment, we embedded a Global Health Book Club assignment within an undergraduate global public health course. The goal of this study was to leverage the pluralistic views, social identities, and demographics within the classroom to explore the effects of introducing a global health book club focused on identity of culture, equity, and power. Furthermore, we sought to explore the use of first-account narratives illustrating the human experience as an instructional strategy to cultivate an empathic understanding of global health threats, while fostering critical consciousness toward one’s positionality within larger social, political, and global contexts. Finally, during this book club students were encouraged to share ideas, topics, and readings for the course, as well as their lived cultural experiences to facilitate dialogue and discussion of areas that their book club may not cover. At the conclusion of the Global Health Book Club, students engaged in a reflective writing assignment. Student responses were analyzed using inductive thematic analysis procedures. Through our analysis, six themes, with several coinciding categories, were identified as salient. The themes include Demonstrated Empathy, Personal Reflection and Growth, Personally Inspired, Immersive Learning Experience, Broadened Perspective, and Provoked Emotion. Our findings support that a Global Health Book Club assignment is a viable and effective mechanism for engaging students in critical reflection, critical motivation and critical action. In cultivating a learning environment that promotes not only student-centered learning but active and critical participation, students were allowed to be agents of their own learning. This work can serve as an exemplary model for other public health educators to engage students in reflective-based assignments regarding their positionality and critical consciousness toward health disparities, inequities and inequalities. By utilizing frameworks conceived out of anti-racism, diversity, equity, and inclusion, our work presents an innovative activity in engaging students in decolonization efforts within global public health practice.